Research on the law of engine compressor blade crack propagation based on operation data - SHI LiZhong; DONG Shuo; LIU XueFeng; CHEN Jian (Jixie qiangdu)
In order to study the crack damage propagation law of rotor blades under complex loads in the actual service of aero-engines, the crack propagation life curve of blades was constructed based on the operational data of aero-engine, and the crack propagation rate formula was established by fracture mechanics theory. Taking the high-pressure compressor blade as an example, the load model of the compressor blade structure was constructed by the fluid-solid coupling method. The Paris， Walker and Newman crack growth rate formulas were used to analyze the three-dimensional crack propagation in the tip region of the compressor blade. The simulation results show that the prediction results of the three crack propagation rate formulas are consistent with the crack propagation curve of the engine operation data in the early stage of crack propagation, which can better describe the crack propagation law of the blade. In the stage of stable crack propagation, the prediction results of Walker and Newman formulas are relatively dangerous, and the prediction results of Paris formula are in good agreement with each other, and can be mutually confirmed with the requirements of damage development control in the manufacturer's technical manual.